2010
DOI: 10.3922/j.psns.2010.2.011
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and circadian rhythms.

Abstract: All mammal behaviors and functions exhibit synchronization with environmental rhythms. This is accomplished through an internal mechanism that generates and modulates biological rhythms. The circadian timing system, responsible for this process, is formed by connected neural structures. Pathways receive and transmit environmental cues to the central oscillator, the hypothalamic suprachiasmatic nucleus, which mediates physiological and behavioral alterations. The suprachiasmatic nucleus has three major inputs: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 141 publications
(183 reference statements)
0
14
0
Order By: Relevance
“…Despite conflicting evidence of activity rhythms in the raphe nuclei, extensive work has demonstrated that release of serotonin (5‐HT) in downstream targets—including SCN, cortex, and surrounding raphe areas—varies across the 24‐hr cycle with peak 5‐HT levels found during the day (Cagampang & Inouye, ; Cagampang, Yamazaki, Otori, & Inouye, ; Quay, ); but see also Crespi & Jouvet (). Furthermore, 5‐HT has been shown to play a large role in the process of nonphotic entrainment in the SCN (for review, see Pontes et al., ). Given the importance of neuronal activity of serotonergic neurons in seasonal affective disorder (Green, Jackson, Iwamoto, Tackenberg, & McMahon, ), a better understanding of how the local midbrain clock regulates neuronal firing is needed.…”
Section: Mesencephalon (Midbrain): Periaqueductal Gray Raphe Nucleimentioning
confidence: 99%
“…Despite conflicting evidence of activity rhythms in the raphe nuclei, extensive work has demonstrated that release of serotonin (5‐HT) in downstream targets—including SCN, cortex, and surrounding raphe areas—varies across the 24‐hr cycle with peak 5‐HT levels found during the day (Cagampang & Inouye, ; Cagampang, Yamazaki, Otori, & Inouye, ; Quay, ); but see also Crespi & Jouvet (). Furthermore, 5‐HT has been shown to play a large role in the process of nonphotic entrainment in the SCN (for review, see Pontes et al., ). Given the importance of neuronal activity of serotonergic neurons in seasonal affective disorder (Green, Jackson, Iwamoto, Tackenberg, & McMahon, ), a better understanding of how the local midbrain clock regulates neuronal firing is needed.…”
Section: Mesencephalon (Midbrain): Periaqueductal Gray Raphe Nucleimentioning
confidence: 99%
“…Furthermore, brain serotonin synthesis and catabolism have their own circadian rhythm, closely related to the SCN. Neuronal serotonin release in the SCN is provided in the absence of photic stimulation, and serotonin levels increase in the raphe nucleus after the beginning of the dark phase [ 107 ]. Tryptophan hydroxylase (TpH), the rate-limiting enzyme in the synthesis of serotonin, is one of the regulators of circadian rhythm in the raphe nucleus.…”
Section: Neurohumoral and Hormonal Regulation Of Circadian Rhythmmentioning
confidence: 99%
“…Furthermore, brain serotonin synthesis and catabolism have their own circadian rhythm, closely related to the SCN. Neuronal serotonin release in the SCN is provided in the absence of photic stimulation, and serotonin levels increase in the raphe nucleus after the beginning of the dark phase (Pontes et al, 2010). Tryptophan hydroxylase (TpH), the ratelimiting enzyme in the synthesis of serotonin, is one of the regulators of circadian rhythm in the raphe nucleus.…”
Section: Neurohumoral and Hormonal Regulation Of Circadian Rhythmmentioning
confidence: 99%
“…Tryptophan hydroxylase (TpH), the ratelimiting enzyme in the synthesis of serotonin, is one of the regulators of circadian rhythm in the raphe nucleus. It is known that TpH peaks during the dark phase, helping the interaction between the serotoninergic system and the SCN through the increment of serotonin levels (Pontes et al, 2010). Also, serotonergic neurotransmission alterations could cause phase shifts and changes in SCN activity affecting the phosphorylation of CLOCK proteins (Zaki et al, 2018).…”
Section: Neurohumoral and Hormonal Regulation Of Circadian Rhythmmentioning
confidence: 99%